Evaluation of Novel Approaches to Software Engineering 17th International Conference, ENASE 2022, Virtual Event, April 25-26, 2022, Revised Selected Papers - Kaindl, Hermann; Mannion, Mike.; Maciaszek, Leszek A. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 17th International Conference on Evaluation of Novel Approaches to Software Engineering, ENASE 2022, held Virtually. The 15 full papers included in this book were carefully reviewed and selected from 109 submissions. They were organized in topical sections as follows: Theory and Practice of Systems and Applications Development; Challenges and Novel Approaches to Systems and Software Engineering (SSE); and Systems and Software Quality.
Theory and Practice of Systems and Applications Development -- An Approach-based on Allen's Interval Algebra to Provision Resources for Disrupted Business Processes -- BPMN4FRSS: An BPMN Extension To Support Risk-Based Development of Forensic-Ready Software Systems -- Evaluating Probabilistic Topic Models for Bug Triaging Tasks -- Software Project Management Approaches Used in the Context of Agile Development: A Systematic Literature Mapping -- Empirical Validation of Entropy-based Redundancy Metrics as Reliability Indicators using Fault-proneness Attribute and Complexity Metrics -- Dynamic link Network Emulation and Validation of Execution Datasets -- Predicting Bug-fixing Time using the Latent Dirichlet Allocation Model with Covariates -- Challenges and Novel Approaches to Systems and Software Engineering (SSE) -- Pull Requests Integration Process Optimization: An Empirical Study -- Identify Javascript Trends in Crowdsourcing Small Tasks -- Assessing Sustainability Impacts of Systems: SuSAF and the SDGs -- Exploiting Metadata Semantics in Data Lakes using Blueprints -- The Ugly Side of Stack Overow: An In-depth Exploration of the Social Dynamics of New Users' Engagement and Community Perception of Them -- Systems and Software Quality -- Better Understanding Diverse End User Website Usage Challenges with Browser-based Augmented Reality Approaches -- An Exploration of Technical Debt Over the Lifetime of Open-source Software -- A New Metric for Multithreaded Parallel Programs Overhead Time Prediction.
Keywords: Software engineering; Database management; Computer programming; Software Engineering; Database Management System; Programming Techniques